The Influence of Digital Marketing and Brand Awareness on Consumer Purchase Decisions at Feedmee.ind, a Micro, Small, and Medium Enterprise (MSME) located in Royal Plaza Surabaya - Musafira Okta Ghina Tsabitah; Supriyono Supriyono (Digital Innovation : International Journal of Management, 2025)
The development of digital technology has transformed marketing patterns, including in the culinary sector. The MSME Feedmee.ind utilizes digital marketing strategies and builds brand awareness to increase consumer purchasing decisions. This phenomenon is relevant to consumer behavior trends, particularly among the younger generation active on social media, making digital marketing a critical factor in business competition. This research aims to determine the influence of digital marketing and brand awareness on the purchasing decisions for the MSME Feedmee.ind at Royal Plaza Surabaya. This study employs a quantitative method with the population consisting of all Feedmee.ind consumers at Royal Plaza Surabaya, using an accidental sampling technique. The research sample comprises 92 respondents selected based on specific criteria. Data analysis was conducted using the Partial Least Squares – Structural Equation Modeling (PLS-SEM) technique with SmartPLS 4 software. The research findings indicate that digital marketing has a positive and significant influence on purchasing decisions. Similarly, brand awareness is also proven to have a positive and significant effect on purchasing decisions. These findings confirm that an interactive and consistent digital marketing strategy, supported by the strengthening of brand awareness, can effectively increase consumer interest and purchasing decisions.